Obtaining EQ-5D-5L utilities from the disease specific Quality of Life Alzheimer’s Disease Scale: Development and results from a mapping study - Rombach, I; Iftikhar, M; Jhuti, G; Gallacher, J; Landeiro, F; Gray, A; ROADMAP Consortium (Springer, 2020)
Purpose: The Quality of Life Alzheimer’s Disease Scale (QoL-AD) is commonly used to assess disease specific health-related quality of life (HRQoL) as rated by patients and their carers. For cost-effectiveness analyses, utilities based on the EQ-5D are often required. We report a new mapping algorithm to obtain EQ-5D indices when only QoL-AD data are available.